Prevalence of untreated asthma in a population sample of 6000 older adults in Bristol, UK. Issue 6 (1st June 2001) - Dow, L; Fowler, L; Phelps, L; Waters, K; Coggon, D; Kinmonth, A L; Holgate, S T
Abstract : BACKGROUND: A study was undertaken to estimate the prevalence of untreated asthma in older adults. METHODS: A cross sectional population based survey of 6000 men and women aged 65 years and over was performed in 21 general practices in north Bristol, south west England. The main outcome measure was untreated asthma as defined by a two stage process comprising a respiratory questionnaire (symptoms suggestive of asthma or doctor diagnosed asthma not receiving respiratory treatment) followed by lung function tests (significant reversibility following bronchodilators or corticosteroids and/or significant within day variability in peak expiratory flow). RESULTS: 4792 of the 6000 participants (80%) completed the respiratory questionnaire and, of those not receiving respiratory treatment, 55 reported a previous doctor diagnosis of asthma and a further 696 had symptoms suggestive of asthma. Lung function testing in 280 of 501 randomly selected individuals from these groups resulted in 38 being defined as having asthma and an estimated population prevalence for untreated asthma of 2.4% (95% CI 1.6% to 3.6%) in men and 1.2% (95% CI 0.7% to 2.1%) in women. Most subjects (84%) with untreated asthma had moderate or severe disease. Untreated asthma was most common in individuals with doctor diagnosed asthma (21%) and those with breathlessness or wheeze (13–20%). CONCLUSION: Untreated asthma in the elderly is a common and important problem. Opportunistic use of appropriate lung function tests in older people with a history of doctor diagnosed asthma or wheeze or breathlessness at rest could identify untreated asthmatics who might benefit from treatment.